The Role of Propensity to Plan on Retirement Savings and Asset Accumulation. (3rd September 2016) - Lee, Jae Min; Kim, Kyoung Tae
Abstract : This study used the 2013 Survey of Consumer Finances (SCF) to identify the role of the propensity to plan on retirement savings and asset accumulation. Based on the theory of propensity to plan, this study proposed two comprehensive indices for propensity to plan by reducing the number of related variables using principal components analysis. Results from ordinary least squares regressions indicated that both retirement savings and net worth increased as the level of propensity to plan increased. This study provides empirical evidence and implications for the role of the propensity to plan on retirement savings and wealth accumulation.